2011
DOI: 10.1016/j.brat.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

EMDR: Eye movements superior to beeps in taxing working memory and reducing vividness of recollections

Abstract: Posttraumatic stress disorder (PTSD) is effectively treated with eye movement desensitization and reprocessing (EMDR) with patients making eye movements during recall of traumatic memories. Many therapists have replaced eye movements with bilateral beeps, but there are no data on the effects of beeps. Experimental studies suggest that eye movements may be beneficial because they tax working memory, especially the central executive component, but the presence/degree of taxation has not been assessed directly. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 25 publications
6
74
0
4
Order By: Relevance
“…In a working memory framework, this would be in line with the finding that either Word games led to relatively fewer intrusions than Tetris, or both Tetris and Word games resulted in relatively fewer intrusions than reactivation-only controls. It is also in line with studies that found a dose–response relationship in that more taxing dual tasks resulted in greater declines in vividness and emotionality of voluntarily retrieved autobiographical memories (Engelhard, Van den Hout & Smeets, 201; Van den Hout et al, 2011), and fewer intrusive memories of aversive pictures (Pearson & Sawyer, 2011). Note that dual task effects on vividness and emotionality of autobiographical memories decreased with too much taxing, suggesting an inverted U-relationship (Engelhard et al, 2011; Van den Hout & Engelhard, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…In a working memory framework, this would be in line with the finding that either Word games led to relatively fewer intrusions than Tetris, or both Tetris and Word games resulted in relatively fewer intrusions than reactivation-only controls. It is also in line with studies that found a dose–response relationship in that more taxing dual tasks resulted in greater declines in vividness and emotionality of voluntarily retrieved autobiographical memories (Engelhard, Van den Hout & Smeets, 201; Van den Hout et al, 2011), and fewer intrusive memories of aversive pictures (Pearson & Sawyer, 2011). Note that dual task effects on vividness and emotionality of autobiographical memories decreased with too much taxing, suggesting an inverted U-relationship (Engelhard et al, 2011; Van den Hout & Engelhard, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have repeatedly shown positive effects for dual tasks on vividness and emotionality ratings of autobiographic memories (e.g. Gunter & Bodner, 2008; Leer et al, 2014; van den Hout et al, 2011). However, contrary to previous research, neither dual-task TGP1 nor dual-task TGP2 reduced vividness and emotionality ratings.…”
Section: Discussionmentioning
confidence: 93%
“…The beneficial effects of dual tasks have been found in healthy volunteers retrieving a negative autobiographical memory when performing eye movements (e.g. Leer, Engelhard, & van den Hout, 2014; van den Hout et al, 2011, 2012), drawing complex figures (Gunter & Bodner, 2008) and mental arithmetic (Engelhard, van den Hout, & Smeets, 2011). In addition, the effectiveness of Eye Movement Desensitization and Reprocessing (EMDR) for PTSD has been explained by WM theory (van den Hout & Engelhard, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to the orienting response is that to store trauma memories in an episodic form taxes working memory and that eye movements competes with such memories for the limited storage capacity which then results in reductions in vividness and subsequently emotional ratings (I. M. van den Hout et al, 2011;van den Hout et al, 2010) EMDR is efficacious for PTSD and trauma patients with or without co-morbid depression and requires little -to-no between session tasks to ensure positive outcomes. This evidence can be added to the growing list of differences between EMDR and CBT that others have also noted including the way exposure is employed in each of the 2 treatment modalities, EMDR's non-directive approach, and the encouragement of free association during trauma recall and distancing.…”
Section: Discussionmentioning
confidence: 99%